Case Report: Complete response to the concurrent neoadjuvant radiation therapy and pembrolizumab in a locally recurrent, chemotherapy-refractory undifferentiated pleomorphic sarcoma of bone - Patel, Brina A.; Smith, Jason T.; Wangsiricharoen, Sintawat; Wang, Wei-Lien; Lin, Patrick P.; Farooqi, Ahsan; Nassif Haddad, Elise F.; Ummed, Kamal; Mericli, Alexander F.; Adelman, David M.; Livingston, John Andrew; Conley, Anthony P. (Frontiers in Oncology, 2026)
Undifferentiated pleomorphic sarcoma of bone (UPS-B) is a rare and aggressive cancer that accounts for a small fraction of bone sarcomas. Compared to both undifferentiated pleomorphic sarcoma of soft tissue (UPS-ST) and osteosarcoma, UPS-B demonstrates lower chemosensitivity and a poorer prognosis, with reported five-year survival rates of only 7.3%. Standard management has generally mirrored osteosarcoma regimens, surgery, multi-agent chemotherapy, and radiotherapy, though the optimal approach remains undefined. In contrast, immune checkpoint inhibitors (ICIs) targeting PD-1/PD-L1 have shown promising activity in UPS-ST but minimal efficacy in osteosarcoma, leaving the role of ICIs in UPS-B largely unknown. We report the case of a 61-year-old male with recurrent, chemotherapy-refractory UPS-B of the left ilium who achieved a complete and durable response with concurrent neoadjuvant pembrolizumab and radiotherapy followed by surgical resection. The patient initially presented with a destructive iliac mass in 2021 and underwent induction with doxorubicin/cisplatin, which was complicated by acute kidney injury and thromboembolic events, followed by hemipelvectomy. He subsequently experienced local recurrence four months postoperatively, confirmed by biopsy. Treatment with high-dose ifosfamide provided no durable disease control, and imaging demonstrated progressive growth. Molecular profiling revealed 90% PD-L1 expression, multiple oncogenic mutations including SMARCA4 and POLE, and a mutational signature consistent with high tumor mutational burden (TMB), suggesting potential immunogenicity. Based on these features and disease progression, he was treated with hypofractionated radiotherapy (42.75 Gy in 15 fractions) concurrently with pembrolizumab for three cycles prior to surgery. Resection in June 2022 demonstrated no viable tumor, consistent with complete pathologic response. The patient has since completed one year of adjuvant pembrolizumab, with ongoing therapy and no evidence of recurrence at 24 month follow-up.